Arthropoda associated to the olive crop in Southern Portugal (Algarve) - Gonçalves, Maria (2017)
The main objective of this work was to study the abundance and diversity of arthropods associated with the olive crop (Olea europea L.), in southern Portugal. The trials were carried out in two different olive groves, one located in Olhão and the other located in Loulé, both in the integrated mode of production. The sampling techniques used in the trials consisted of pitfall traps, yellow sticky traps with and without sexual pheromone, delta pheromone traps (the pheromone lure in the trap attracts the adult moth) and sampling of leaves, flowers and fruits. The results obtained in the trials indicate that the arthropods associated with the olive crop belong to the following classes: Arachnida (order: Araneae), Chilopoda, Entognatha (order: Collembola) and Insecta. Among these groups, most specimens belonged to the class Insecta, followed by Arachnida, Entognatha and Chilopoda. Regarding to the Insecta class the orders and families that inhabit the olive ecosystem are: Diptera (Syrphidae and Tephritidae), Coleoptera (Carabidae, Chrysopidae, Curculionidae and Staphylinidae), Hemiptera (Anthocoridae and Miridae), Homoptera (Coccidae and Psyllidae), Hymenoptera (Braconidae, Encyrtidae, Eulophidae, Trichogrammatidae and Formicidae), Lepidoptera (Hyponomeutidae), Neuroptera (Chrysopidae) and Thysanoptera (Phlaeothripidae).